Optimization of Samapta Dialogic Patrol to Prevent Motor Vehicle Theft in the Jurisdiction of Brebes Police Resort - Abidin, Amarullah (Indonesian Journal of Police Studies, 2024)
The author's final project raises the issue of "Why is Samapta Dialogical Patrol to Prevent Motor Vehicle Theft in the Jurisdiction of the Brebes Police Not Optimal?". This final project aims to find differences between what should have happened and what actually happened in the implementation of dialogic patrols and to find efforts to optimize the implementation of dialogic patrols carried out by the Satsamapta Polres Brebes in order to prevent criminal acts of theft in the jurisdiction of the Brebes Police. This study used a qualitative approach with a case study type of research by observing, interviewing informants and studying documents. This study uses management theory and competency theory as well as the concepts contained in the laws and regulations governing Satsamapta patrol procedures. The Brebes Police Samapta Unit in carrying out dialogic patrols to prevent theft is still not by the SOP. There was no security situation and conditions message that should have been planned prior to implementation. Then cooperation with the police has not yet been established so that patrol activities do not reach remote areas. The leadership's supervision of the implementation of the Brebes Police Satsamapta dialogic patrols is still relatively low. The competence possessed by members of the Brebes Police Satsamapta in carrying out dialogic patrols is still minimal, seen from the number of personnel who have attended vocational education, especially in the field of patrols and there are still members who commit several violations in carrying out their duties. For this reason, efforts are needed to optimize the implementation of dialogic patrols by the Satsamapta Polres Brebes in preventing the crime of theft through providing a reward and punishment system for members, enforcing SOPs for implementing dialogic patrols, collaborating with the police, providing training for members, and strengthening supervision from leaders.